Reinforcement learning based autonomous vehicle for exploration and exploitation of undiscovered track - Issa, Razin Bin; Rahman, Md. Saferi; Das, Modhumonty; Barua, Monika (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.